2005
DOI: 10.1167/iovs.04-1362
|View full text |Cite
|
Sign up to set email alerts
|

Functional Analysis of the p53 Pathway in Response to Ionizing Radiation in Uveal Melanoma

Abstract: Expression of p53 and upstream signaling to p53 in response to radiation-induced DNA damage appear to be intact in most uveal melanomas. In contrast, functional defects in the p53 pathway downstream of p53 activation appear to be common. Further elucidation of p53 pathway abnormalities in uveal melanoma may allow therapeutic interventions to increase the radiosensitivity of the tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 26 publications
1
37
0
Order By: Relevance
“…The p53 pathway is functionally blocked by its inhibitor MDM2 [13][14][15]29,30 BCL-2 Defects in the Bcl2 pathway in UM contribute to apoptosis resistance 11,14,29 PTEN downregulation The PI3K-AKT prosurvival pathway is constitutively activated in UM to avoid apoptosis 19,20 Produce insulin-like growth factor (IGF- …”
Section: Avoid Apoptosis P53 Pathway Alterationsmentioning
confidence: 99%
See 2 more Smart Citations
“…The p53 pathway is functionally blocked by its inhibitor MDM2 [13][14][15]29,30 BCL-2 Defects in the Bcl2 pathway in UM contribute to apoptosis resistance 11,14,29 PTEN downregulation The PI3K-AKT prosurvival pathway is constitutively activated in UM to avoid apoptosis 19,20 Produce insulin-like growth factor (IGF- …”
Section: Avoid Apoptosis P53 Pathway Alterationsmentioning
confidence: 99%
“…[11][12][13]29,30,90 The Rb protein is constitutively hyperphosphorylated and functionally inactivated in most UM, probably as a result of cyclin D1 overexpression in about 65% of cases. 12,14,15 ( Figure 1; Table 1) The role of CDKN2A promoter hypermethylation, as an additional mechanism of Rb inactivation, is controversial as the frequency of hypermethylation of this gene varies between 4 and 33% of UM.…”
Section: Molecular Pathway Defects In Primary Ummentioning
confidence: 99%
See 1 more Smart Citation
“…After 24, 48, and 72 hours of NGF treatment, cells were collected and nonadherent cells were counted manually using the trypan-blue exclusion method. 16 …”
Section: Cd34 + Cell Proliferationmentioning
confidence: 99%
“…In vitro studies have shown that downstream defects in the p53 pathway may be involved in resistance to apoptosis, even though the radioresistance of UM is unlikely to be attributed to a single genetic defect. 32 UM cell lines show a wide range of radiosensitivity, which may be explained by varied induction of apoptosis, and cell cycle disruption. 33 The mechanism underlying the synergistic effect of COX-2 inhibitors and radiation remains elusive.…”
Section: Eyementioning
confidence: 99%